Principles and Trade-Offs when Making Issuance Choices in the UK (OECD Working Papers on Sovereign Borrowing and Public Debt Management, 2011)
This paper sets out: (i) the principles underpinning debt management policy in the UK; (ii) the key factors influencing annual issuance decisions; and (iii) how some of those factors require judgements to be made in determining appropriate trade-offs. Key factors influencing annual issuance decisions are determined in accordance with the debt management objective. As part of this assessment the UK Government undertakes an analysis of the demand conditions in the gilt market and implications for the cost of issuance. Other factors such as market management and portfolio diversification considerations are also taken into account as well as practical and operational issues associated with any issuance strategy..